Jauhar Straw listed in the 10 best business groups of i-ProCom - Nor Salwana, Mohammad Idris (2021)
KUANTAN, 8 September 2021 - Jauhar Straw group from Universiti Malaysia Pahang (UMP) was selected among the top ten Business Plans and Business Model Canvas (BMC) in the Idea, Product & Commercial (i-ProCom) programme through the innovation of friendly straws that replaces plastic straws (Jauhar Straw).